2017
DOI: 10.6007/ijarbss/v7-i6/3025
|View full text |Cite
|
Sign up to set email alerts
|

The Factors Affecting Teacher Leadership in Malaysian Primary Schools

Abstract: This study aims to identify the level of leadership among teachers and the factors that are affecting teacher leadership. A total of 250 teachers from 25 primary schools participated in this study. This study used questionnaire for data collection. The data were analysed by using descriptive and correlation tests to investigate the relationship between the focused factors. The results showed that the level of leadership among teachers is moderate. The findings also showed that there is a significant relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…That there was a significant relationship between school culture and teacher attitudes and personality factors with teacher leadership. Meanwhile, management support factors do not show a significant relationship with teacher leadership [11].…”
Section: ) There Is a Direct Effect Of Teacher's Leadership Toward Cmentioning
confidence: 78%
“…That there was a significant relationship between school culture and teacher attitudes and personality factors with teacher leadership. Meanwhile, management support factors do not show a significant relationship with teacher leadership [11].…”
Section: ) There Is a Direct Effect Of Teacher's Leadership Toward Cmentioning
confidence: 78%
“…Research shows that school culture plays an important role in improving teacher leadership (Harris and Kemp-Graham, 2017; Nguyen et al. , 2020; Yusof et al. , 2017; Öztürk and Şahin, 2017; Wang and Ho, 2020; Wang and Zepeda, 2013; Wynne, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Professional cooperation among teachers in schools supports the professional development of teachers. Research shows that school culture plays an important role in improving teacher leadership (Harris and Kemp-Graham, 2017;Nguyen et al, 2020;Yusof et al, 2017;€ Ozt€ urk and S ¸ahin, 2017;Wang and Ho, 2020;Wang and Zepeda, 2013;Wynne, 2004). Teacher leadership culture should be nurtured through sharing leadership.…”
Section: Teacher Leadership Culturementioning
confidence: 99%
“…This finding was in line with the study findings from (1) Rahim ( 2018 Basri, Pehei and Asimiran (2016) were similar to the findings of this study where the level of teacher leadership in schools was at a high level. On the other hand, studies conducted by (Misdi, Sumintono, & Abdullah, 2019) and (Yusof, Vyapuri, Jalil, Mansor, & Noor, 2017) reported that the level of teacher leadership was still at a moderate level among teachers in Malaysia.…”
Section: Level Of the Practices Of Learning Organization (Dloq)mentioning
confidence: 95%